EFFECTIVE METHODS OF PREPARING CHILDREN WITH AUTISM FOR SCHOOL EDUCATION (World Bulletin of Education and Learning, 2026)
This article highlights the factors of ensuring continuity of work on the correct diagnosis of children with autism syndrome, effective organization and conduct of correctional and developmental work that ensures the elimination of deficiencies in behavior and general development, as well as their successful adaptation to social life.
Keywords: Autism spectrum defect, ASD, autism syndrome, symptom, stereotype, diagnosis, zone of immediate development of the child, early intervention, Demonstrative stage, diagnostic, biographical, observational, mental, experimental, individual, follow-up, joint, PESC, cultural, adaptive, ability, inclusive, visual, social narrative, communication, sensory integration, correction.